Vapour-liquid equilibrium - HaIla, Eduard (Pergamon, 1967)
Vapor-Liquid Equilibrium, Second Edition covers the theoretical principles and methods of calculation of equilibrium conditions from various experimental data and the elements of measuring technique, as well as the instruments for the direct determination of the equilibrium compositions of the liquid and vapor phases of the system. The book discusses the relations necessary for the thermodynamic treatment of the equilibrium between the liquid and vapor phase of a system; the concept of an ideal solution and auxiliary thermodynamic functions; and the activity and the activity coefficient. The.